Diversity, nutrient contents and production of forage plants in an integrated cattle livestock-oil palm plantation in East Kalimantan, Indonesia - TAUFAN PURWOKUSUMANING DARU; WIDI SUNARYO; HENNY PAGORAY; SUHARDI SUHARDI; HAMDI MAYULU; IBRAHIM IBRAHIM; APDILA SAFITRI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Daru TP, Sunaryo W, Pagoray H, Suhardi, Mayulu H, Ibrahim, Safitri A. 2023. Diversity, nutrient contents and production of forage plants in an integrated cattle livestock-oil palm plantation in East Kalimantan, Indonesia. Biodiversitas 24: 1981-1989. The integration of cattle livestock rearing into oil palm plantations delivers various benefits. The livestock management can reduce the weeds and add organic nutrients to the plantations, while the understorey vegetation grow under the oil palm trees can be used as forage for the livestock. Several studies reported that the age of oil palm plantations affects forage production in integrated cattle livestock palm oil plantations. From an ecological standpoint, the diversity of plant species and the level of forage production varies based on the age of the oil palm trees. Therefore, this study aimed to determine the diversity, composition, nutrient contents, forage production and carrying capacity of understorey vegetation in oil palm plantations at different ages of 3, 7, and 10 years in Paser District, East Kalimantan Province, Indonesia. A total of 29 plant species from 13 families were found under oil palm plantations, of which 14 species (48.27%) are palatable to cattle livestock. The results showed that the diversity of plant species decreased along with the increasing age of oil palm trees, but they were able to meet the needs of livestock. In the 3, 7, and 10-year-old plantations, the diversity index (H') was 1.491, 1.634, and 2.099, with evenness index (E) of 0.538, 0.589 and 0.757; as well as the dominance index of 0.15, 0.30, and 0.18, respectively. Narrow-leaved forage plant species dominated the understorey vegetation and increased along with the age of oil palm plantations due to the ability to adapt to environmental conditions. The low forage production under the different ages of oil palm plantations caused a low carrying capacity to support livestock feed, namely 0.87, 0.56, and 0.36 Animal Unit (AU) ha-1 per year in the 3, 7, and 10-year-old plantations. Nonetheless, Crude Protein (CP) and total digestible nutrients can meet the basic life needs of livestock. The results of this study imply that oil palm plantations in Paser District can be applied as livestock rearing with different carrying capacities based on the different ages of oil palm plantations.